The collaborative work between engineers and health staff for development of digital health projects: A vision to the future to achieve success (2018)
The trends in Information and Communication Technology (ICT) have fomented a joint work between health team and engineers, with the purpose of develop devices that allow the exchange of data in a space that facilitates the interaction and obtaining patient information. However, this is not an explicit field in the technology of health information research. At present, the e-health has been strengthened, but this field still requires an enhanced strategy for improving collaborative work to design of mobile platforms, information clouds, web platforms etc. To this, we realize a systematic review about interdisciplinary teamwork between different researches, such as engineers and some areas of health workers to implement a digital system to prevent, diagnose and provide, using technologies mention above. This review presents an overview of the collaborative work responding to three questions generated during the study.